The Effect of Using Picture Series on Students’ Writing Competence on Recount Text on Smpn 3 Negara in The Academic Year 2025/2026 - Ridho, Aditya; Dewi, Komang Ayu Krisna (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the effect of using picture series on the ability to write recount texts in seventh-grade students at SMP N 3 Negara and to determine their writing skill levels. In this study, the researcher used a form of quasi-experimental method. The researcher selected two classes, one as the experimental class and one as the control class, using a pre-test and post-test design. The treatment, which involved the use of picture series, was given before the post-test was conducted. The data analysis technique used was the t-test. The research results show that there is effectiveness in using picture series as an aid in teaching recount text writing. The data in this chapter shows that the average score of students' recount text writing skills in the experimental class before using picture series was 65.28, and after the treatment, it increased to 80.28. This indicates a significant difference before and after the treatment. Meanwhile, in the control class that did not use picture series, the average score only reached 55.5. Based on these results, it can be confirmed that the use of picture series is able to help students overcome problems related to writing skills.